The man who (almost) controlled the world: the fantastic in the work of Juan José Millás (XXI Century. Spanish Literature and Culture, 2007)
In his fantastical narrations, Juan José Millás proposes to abolish the habitualconception that we have designed in order to comprehend and represent reality,introducing in the latter dark zones that are hidden behind the simple appearances ofthe day-to- day. In this article, beginning with the study of his brief narrative, I havetried to establish the fantastical poetics of Millás, showing which are the themes,reasons and recurring formal elements that the author utilizes to provoke the conflictbetween the real and the impossible.
Keywords: Novel; fanttastical; brief narrative; Millás